Application of Augmented Reality in Food Ordering System - Putu Anggi Suryantari; Rendi Panca Wijanarko; Seftin Fitri Ana Wati, S.Kom., M.Kom; Amalia Anjani Arifiyanti, S.Kom., M.Kom; Anita Wulansari, S.Kom., M.Kom; I Gusti Ayu Sri Deviyanti, ST., MT (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2023)
Current digital trends put the need for information at the forefront, making information processingbetween authorities and organizations a priority. Information is a collection of data that has beenprocessed for use in future decision-making processes. When combined, they form an informationsystem. In the economic world, several food-related businesses have implemented informationsystems in their business fields related to data processing systems to carry out computerizedcommercial transactions. However, there are still many businesses that perform traditional serviceswith pencil and paper and have not been able to implement innovative ordering systems based ontechnological developments. One of the businesses experiencing this problem is Dapoer WidyaRestaurant. This study aims to form an ordering system with the PHP programming language and isdesigned using UML models and Augmented Reality (AR)-based menu innovations using Vuporia andUnity3D. System design is built by the SDLC (System Development Life Cycle) method. The result ofthis study is an ordering information system that includes table determination, integrated transactionreports for Dapoer Widya Restaurant staff, and AR-based menus that display 3D views of the menuserved.Keywords: ordering system, menu, augmented reality, SDLC